Following the Cap-Figure in Majapahit Temple Reliefs - Kieven, L. (Verhandelingen van het Koninklijk Instituut voor Taal-, Land- en Volkenkunde, 2013)
This title is available online in its entirety in Open Access. This publication provides a new understanding of the religious function of the East Javanese temples. The study of the cap-figures and their symbolism yields an outstanding contribution to the uniqueness of Majapahit culture.